2005
DOI: 10.1007/s10517-005-0322-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antitumor Efficiency of Photodynamic Therapy with Photoditasine and Photoenergy Density

Abstract: We studied the effect of photodynamic therapy with photoditasine at different protocols of photoenergy exposure on morphofunctional parameters of M-1 sarcoma. It was found that proliferative activity of tumor cells (evaluated by immunostaining for PCNA) nonlinearly decreases after exposure to 150, 300, and 600 J/cm2. The main form of cell death during the early period after photodynamic therapy was direct photocoagulation necrosis caused by destruction of sensitized cell structures and ischemic necrosis develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
2
11
0
6
Order By: Relevance
“…Since cell damage is obviously so profound that repair mechanisms are not operative, death pathways are eventually activated. As reported in part previously [52][53][54], transcripts of cyclin family genes CCNC, CCND1 and CCNG1 as well as of PCNA, a protein crucial for DNA replication, were markedly reduced after PDT in our model thereby possibly leading to a diminished proliferative activity. However, the observed downregulation of cyclininteracting transcription factor E2F1 may also directly promote cell death, as reported previously for PC-3 cells [55].…”
Section: Discussionsupporting
confidence: 78%
“…Since cell damage is obviously so profound that repair mechanisms are not operative, death pathways are eventually activated. As reported in part previously [52][53][54], transcripts of cyclin family genes CCNC, CCND1 and CCNG1 as well as of PCNA, a protein crucial for DNA replication, were markedly reduced after PDT in our model thereby possibly leading to a diminished proliferative activity. However, the observed downregulation of cyclininteracting transcription factor E2F1 may also directly promote cell death, as reported previously for PC-3 cells [55].…”
Section: Discussionsupporting
confidence: 78%
“…As shown in Figure d, compared to control groups, there were many fewer PCNA positive cells in the AuNC@DHLA TP-PDT group, indicating lower levels of tumor cell proliferation. Our results were consistent with previous research which showed that PDT impaired tumor cell proliferation . Taken together, the above results demonstrate that AuNC@DHLA TP-PDT is highly effective in inhibiting the growth of xenograft tumors.…”
Section: Resultssupporting
confidence: 93%
“…It was interesting to observe that in tumors treated with methylene blue nanoparticles, the percentage of PCNA + cells was less than that in other control groups, indicating lower levels of cell proliferation. Previous research has shown impaired tumor cell proliferation after PDT [35]. …”
Section: Discussionmentioning
confidence: 99%